STATISTICAL OPTIMIZATION AND SENSITIVITY ANALYSIS ON MECHANICAL PROPERTY IN HYDRO FRACTURING PROCESS - Guruprasad, B.; Ragupathy, A.; Badrinarayanan, T. S.; Sankaralingam, T. P. (European Scientific Journal, ESJ, 2013)
In the hydrofraturing process, the parameters such as Pressure in N/mm2, Temperature in ºC, Injection hole diameter in mm play a major role in determining the fracture length during the hydrofraturing process. A central composite rotatable design with three factors and three levels was chosen to minimize the number of experimental conditions. An empirical relationship was established to predict the fracture length(mm) of the hydrofraturing process by incorporating independently controllable hydrofraturing process parameters. Response surface methodology (RSM) was applied to optimize the process parameters to attain maximum fracture length (mm). Sensitivity analysis was also carried out to understand the impact of each process parameters on Fracture length.